“Notes from England”: Values of Character Education as Junior High School Teaching Materials - Atikah Anindyarini (Al-Ishlah: Jurnal Pendidikan, 2022)
This research aims to analyze the values of character education contained in Notes from England and its relevance to teaching materials in Junior High School (Indonesian: Sekolah Menengah Pertama or SMP). This book tells the struggle of Ario Muhammad and Fissilmi Hamida (students coming from Indonesia) in chasing their dream to continue their studies in England. The research data was that of narration and dialogue taken from Notes from England by Ario Muhammad and Fissilmi Hamida, containing character education value.  The technique of collecting data used was library study and interview. For data validation, this research employed method triangulation by using document analysis through observing documents and interviewing teachers. Data analysis in this research was carried out using an interactive model of analysis encompassing data reduction, data display, and conclusion drawing. Based on the data analysis on Notes from England, the following conclusions can be drawn: (1) values of character education contained in this book are religiosity, discipline, hard work, creativity, independence, curiosity, friendliness/communicativeness, reading habit, and social care, (2) Notes from England contains many high values of character education, and thereby it is relevant to Literature Teaching materials in the 9th grade of Junior High School (SMP).